The role of intellectuals in the development of women's rights in South Kurdistan (1921-1968) - Fatah, Dr. Hunar Rostam (Sulaimani Journal for Humanities, 2026)
In the first half of the 20th century, the role of women and the heart of humanity for women in South Kurdistan was a prominent aspect of the social reform process. Therefore, we see a significant number of articles and researches They have the right to all kinds of freedom, like the other half, to improve their lives and their community, and to use their strengths and abilities, which will certainly bring the greatest benefit to the community. Therefore, from the understanding of Kurdish culture, a society in which women do not have the right to live like men and there is a difference between them can never be called a developed society. Following the method of historical analysis and presenting the issues, the researcher tried to highlight the efforts of Kurdish intellectuals during the years (1921-1968) on issues such as marriage, criticism of rural society for not giving their daughters rights at home, misrepresenting polygamy and demanding divorce from women. This is in addition to defending women's political rights and advocating women's participation in the electoral process and political work, as well as talking about not depriving women of education as a solution to many problems, creating a free economy for women through freedom of work. Thus, thanks to the social struggle of intellectuals and the awakening of Kurdish society, women began to participate in the political, economic and cultural spheres in South Kurdistan in the late 1950s and early 1960s
Keywords: Intellectuals; South Kurdistan; Womens Rights; Social Change